Implications of quality deterioration for public foodgrain stock management and consumers in Bangladesh - Dorosh, Paul A.; Farid, Naser (International Food Policy Research Institute, 2003)
In the late 1990s, government policy in Bangladesh shifted in favor of increased public foodgrain stocks, setting official minimum stock targets of 1.0 to 1.2 million tons, as compared to operational targets of about 700 to 800 thousand metric tons in the early 1990s. Because no mechanism for stock rotation involving simultaneous buying and selling grain at a wholesale level exists, higher stock levels with no increase in distribution led to an increase in average age of stocks and problems of stock quality deterioration. This paper extends earlier analyses of stock policy by focusing on a key aspect of stock management in Bangladesh: the economic costs of stock quality deterioration in storage, including the implicit costs to recipients of Public Food Distribution System (PFDS) foodgrain. Using market prices to value procurement and distribution of rice and wheat, consumer and producer subsidies accounted for 57.4 and 20.9 percent, respectively, of net outlay in 2000/01. Implicit losses to rice consumers due to quality deterioration were significant in 2000/01: about 1.05 billion Taka (about 19 million dollars), equal to 10.9 percent of total net outlay on rice of the PFDS. Analysis of the costs and benefits of alternative stock targets based on calculations of the minimum age of stock on a monthly basis indicates that moderate increases in the size of stock (e.g. 200 thousand tons), lead to only small net marginal outlays. However, unless procurement and distribution are also raised, the age and quality of the stock for distribution deteriorates, resulting in significant losses to program recipients.